Chondrosarcoma of the larynx: a case report - Şenol Civelek; İbrahim Sayın; İbrahim Ercan; Fevziye Kabukçuoğlu; Suat Turgut (Turkish Archives of Otorhinolaryngology, 2006)

(untitled)
Chondrosarcoma of the larynx is rare. We report a case of 74-yearold man who had been evaluated for hoarseness at another clinic. A laryngeal lesion had been found in endoscopic examination. A biopsy of the laryngeal lesion was consistent with tumoral infiltration with chondromatous spaces. He was referred to our clinic for further evaluation. The patient underwent tracheotomy and surgical excision by endolaryngeal approach. Histopathological analysis of surgical specimen revealed low-grade chondrosarcoma. The diagnostic and therapeutic aspects of this case are discussed.